The Language of Erasure: Neutralization Techniques in Contemporary South African Marital Rape Judgments - Karimakwenda, Nyasha (Violence against women, 2021)
This article investigates how the rape myths that underpinned the marital rape exemption in South Africa until 1993 have filtered into contemporary legal discourse. Through a feminist sociolegal framing, I integrate multidisciplinary tools that counter simplistic conceptions of rape myths and highlight how myths are locally and culturally contingent. With this foundation, I apply neutralization theory to the judicial language of marital rape cases to explicate how patriarchal caricatures of sexual violence transition from the social sphere into the legal sphere. This exercise illuminates how judges and rapists draw upon the same culturally sanctioned language and techniques to justify marital rape.